Gaya Bahasa Hiperbola dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer - Aprila, Tri Mike (MAN 4 Kota Pekanbaru, 2022)
Bumi Manusia is one of the best-seller novels works by Pramoedya Ananta Toer, which has many styles of hyperbole with exciting diction. Pramoedya Ananta Toer's fame as a novelist and his kind personality finally made this novel into a film in 2019. The specialty of this novel should be implemented as a life value, especially by teenagers today. This article aims to analyze the function and meaning of the hyperbole language style contained in the Bumi Manusia novel. This qualitative article used a descriptive method. The data were obtained from words related to hyperbole in this novel. The main instrument is the researcher himself, who uses this novel as a data source. Based on the analysis results, there are 94 hyperbolic language style data. So, it can be concluded that the stylistic function of hyperbole writers tends to apply poetic parts. Meanwhile, in aspects of the meaning of figurative languages, the author succeeds in using denotative and metaphorical meanings in telling the events.